Application of UPFC to Improve the LVRT Capability of Wind Turbine Generator - Alharbi, Yasser Mohammed R; Yunus, A.M.; Abu-Siada, Ahmed (Institut Teknologi Sepuluh Nopember (ITS), 2012)
Variable speed wind turbine generators installation has been significantly increased worldwide in the last few years. Voltage sag at the grid side may call for the disconnection of the wind turbine from the grid as under such faults it may not comply with the recent developed grid codes for wind energy conversion systems (WECS). In this paper, a Unified Power Flow Controller (UPFC) is applied to improve the low voltage ride through (LVRT) capability of doubly fed induction generator (DFIG)-based WECS during voltage sag at the grid side. Simulation is carried out using MATLAB/Simulink software. Results show that UPFC can significantly improve the LVRT capability of DFIG-based WECS and hence maintaining wind turbine connection to the grid during certain levels of voltage sag at the grid side.